Finite element study of sagittal fracture location on thoracolumbar fracture treatment - Cui, Xilong; Zhu, Junjun; Yang, Wanmei; Sun, Yuxiang; Huang, Xiuling; Wang, Xiumei; Yu, Haiyang; Liang, Chengmin; Hua, Zikai (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Posterior internal fixation is the main method used for the treatment of thoracolumbar fractures. Fractures often occur in the upper 1/3 of the vertebral body.However, they can also occur in the middle or lower 1/3 of the vertebral body. At present, there is no report discussing the potential effects of sagittal location on instrument biomechanics or surgical strategy. The object of this study was to investigate the effect of the sagittal location of the fracture region of the vertebral body on the biomechanics of the internal fixation system and surgical strategy.Methods: A finite element model of the T11-L3 thoracolumbar segment was established based on a healthy person's CT scan. Different sagittal fracture location finite element models were created by resection of the upper 1/3, middle 1/3, and lower 1/3 of the L1 vertebral body.Three surgical strategies were utilized in this study, namely proximal 1 level and distal 1 level (P1-D1), proximal 2 level and distal 1 level(P2-D1), and proximal 1 level and distal 2 levels (P1-D2). Nine fixation finite element models were created by combining fracture location and fixation strategies. Range of motion, von Mises stress, and stress distribution were analyzed to evaluate the effects on the instrument biomechanics and the selection of surgical strategy.Results: In all three different fixation strategies, the maximum von Mises stress location on the screw did not change with the sagittal location of the fracture site; nevertheless, the maximum von Mises stress differed. The maximum rod stress was located at the fracture site, with its value and location changed slightly. In the same fixation strategy, a limited effect of sagittal location on the range of motion was observed. P2D1 resulted in a shorter range of motion and lower screw stress for all sagittal locations of the fracture compared with the other strategies; however, rod stress was similar between strategies.The sagittal location of a fracture may affect the intensity and distribution of stress on the fixation system but does not influence the selection of surgical strategy.